Antibacterial Activity of Acetone Coconut Husk (Cocos Nucifera Linn) Extract Against Staphylococcus Aureus and Escherichia Coli Bacteria - Irawan, Ade; Ulfah, Mariam; Efriani, Like; Hadi, Ismanurrahman; Adiyas Putra, Teguh; Puspitasari, Ayu (Jurnal Medisci, 2023)
Coconut plant (Cocos nucifera Linn) is an annual plant that is most beneficial to the people of Indonesia, because almost all parts of the plant can be utilized and used for medicine and daily needs. Part of the coconut plant, namely coconut fiber which is considered as waste, can be used as an antibacterial agent because it contains tannin compounds or also called tannic acid which is a complex chemical compound consisting of several polyphenolic compounds which act as antibacterial and antiviral. The purpose of this study was to determine the antibacterial activity of coconut coir acetone extract (Cocos nucifera Linn) against the growth of Staphylococcus aureus and Escherichia coli bacteria. The method used is disc diffusion (Kirby and Bauer test). Coconut coir powder (Cocos nucifera Linn) was macerated with acetone for 3 x 24 hours. Furthermore, the antibacterial test of coconut coir extract (Cocos nucifera Linn) was carried out against Staphylococcus aureus and Escherichia coli bacteria. Chloramphenicol as a positive control and dimethyl sulfoxide (DMSO) was used as a negative control. The results of antibacterial activity that have been carried out show that coco coir extract (Cocos nucifera Linn) with a concentration of 60% is the highest concentration of inhibition zone diameter between 20% and 40% with an average inhibition zone diameter of 11.7 mm against Staphylococcus aureus bacteria and Escherichia coli and belongs to the category of strong sensitivity.